EPID-12. PRIMARY PAEDIATRIC BRAIN TUMORS IN SINGAPORE: A 17-YEAR SOUTHEAST-ASIAN PERSPECTIVE ON EPIDEMIOLOGY AND OUTCOMES. Issue 2 (22nd June 2018) - Liu, Jiani Sherry; Low, Sharon Yin Yee; Seow, Wan Teow; Low, David; Leong, May Lian; Yeo, Tseng Tsai; Chou, Ning; Kimpo, Miriam; Nga, Vincent
Abstract: Epidemiological studies comparing primary pediatric brain tumors (PBTs) worldwide with various sub-regions in Asia have reported varying disease patterns, likely secondary to genetic susceptibilities and environmental insults. We describe, for the first time, PBT epidemiology in Southeast-Asian, a population distinct from other Asian sub-populations. A retrospective review of 480 patients, diagnosed over a 17-year period in Singapore public pediatric hospitals, was performed to determine: tumor histopathology, location, age distribution and survival rates. Medulloblastoma (19.6%) was the most common subtype, followed by pilocytic astrocytoma (13.5%) and germ cell tumors (9.8%). 42% of PBTs was treated via surgery alone, whereas 53% with surgery/biopsy+adjuvant treatment. The overall survival for all PBTs is 93% at 1-year (1YSR) and 77% at 5-years (5YSR). The 1YSR of medulloblastoma was 73% and 5YSR 71%. The median length of survival is 1-year for those who died of disease, while those who survived>3 years all went into remission, highlighting two extremes in prognosis of medulloblastoma here. Meanwhile, OS and PFS varied for medulloblastoma patients diagnosed at <3-years-old, compared to those aged≥4-years-old. Other than limited use of radiotherapy in infants, this might reflect different frequencies of genetic mutations that predispose infants in Singapore to develop more aggressive medulloblastoma subtypes, given that this age-group more frequently had recurrences/metastasis. This is despite their symptomatic interval till diagnosis being similar to the group that went into remission. There is hence, a need to investigate and elucidate high-risk genetic loci in this population to identify novel molecular targets in biologic therapy, especially for infants.